A Pragmatic Study of Corporate Apologies for Impression Management: A Case of Chinese Food Industry - Zhou, Kexin; Xu, Zhanghong (International Journal of Linguistics, 2022)
Some of Chinese corporations in food industry have recently faced sharp criticism for their illegal operation or unethical behavior. To deal with such crisis, these corporations are inclined to manage their public impressions by issuing apology statements. Serious as these problems are, yet scarce research has focused on the impression management of Chinese corporations through apologies. This paper aims to make a pragmatic analysis of apology strategies employed by Chinese food companies for impression management, drawing upon the framework of Jones and Pittman’s (1982) impression management strategies and Blum-Kulka and Olshtain’s (1984) theory of CCSARP. Based on a self-built corpus of 50 apology statements issued by Chinese food companies, the paper identified different apology strategies and their accompanying linguistic features through discourse analysis. The results show that IFIDs and offer of repair are two of the most common strategies in Chinese corporate apologies, whereas taking on responsibility is less frequently used. The apology strategies are often accompanied with such linguistic features as person deixis, honorifics, intensification and repetition. Chinese companies adopt these diverse apology strategies and linguistic features for the sake of impression management, which is realized by using such strategies as ingratiation, self-promotion, exemplification and supplication. Finally, the paper provides insights into the understanding of crisis management and corporate communication practice online.